Influence of brassinosteroids on metabolites of Raphanus Sativus L. - Vidya Vardhini, B; Sujatha, E; Seeta Ram Rao, S (Journal of Phytology, 2012)
The effect of 24-epibrassinolide and 28-homobrassinolide on the soluble proteins, nucleic acids (DNA and RNA) and carbohydrate fractions (reducing sugars, non-reducing sugars and starch) of radish was studied. Brassinosteroids elevated the soluble proteins of radish. Nucleic acids (DNA and RNA) were also increased by brassinosteroid- application. Increased levels of carbohydrates in terms of reducing sugars, non - reducing sugars and starch was also observed.Â